The Expert Witness in Criminal Cases in France, Germany, and Italy - Ploscowe, Morris (Law and contemporary problems, 1935)
This paper addresses the impact of social capital on the status attainment process of young people at the start of their careers and examines how social class, gender and ethnicity affect the accumulation of social capital and thereby labour market stratification of young people. A sample of young Swedes graduating from vocational schools and universities between 2005 and 2006, was surveyed via the telephone about their experiences acquiring jobs. Two research questions are posed: (i) Which characteristics (class, gender and ethnicity) affect young people's access to more social capital? (ii) How is social capital rewarded in the labour market? The results show that being female, coming from the lower social classes and being a member of a stigmatized immigrant groupare associated with a substantial social capital deficit. When socioeconomic and demographic backgrounds as well as the human capital of respondents are controlled, social capital is positively associated with salary level. The results indicate that social capital is a significant factor in the stratification process of young people